The Dual Nature of Motivation: Intrinsic and Extrinsic Drivers in Second Language Learning - Liu, Yuqing (Transactions on Social Science, Education and Humanities Research, 2024)
Motivation is one of the key factors affecting the learning effect. Based on this, how to improve and stimulate learning motivation is of great practical significance. By correctly grasping the students’ motivation, teachers can target the daily teaching work and make it more effective. In today’s social environment, how to cultivate and stimulate students’ learning motivation is what educators should try and explore. Teachers must convince learners that they are willing to do what they are supposed to do. This paper conducts a systematic review of the research on learning motivation in the field of education in recent years, focusing on the relevant definitions of intrinsic and extrinsic motivation analyzed. It also analyzes the importance of motivation in the learning process of second language acquisition and the degree of its influence. Finally, it concludes how to motivate scholars in the learning process. Motivate and cultivate scholars’ learning motivation in order to improve learning achievement.